Enhancing Architectural Representations in 3D Virtual Reality: Building Denotative and Connotative Meanings - Aydin, Erdal Devrim; Tong, Togan (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2019)
Virtual reality, since being a new form of architectural representation; when compared to traditional forms of representations, is a medium of representation which the narrative techniques are still in the process of developing. In traditional forms of representation, the viewer is actively directed in both the navigation and view, while in the architectural representations in the virtual reality medium, the viewer who now becomes the user, is left to her/his own personal decisions. Hence, the examples produced in the field of virtual reality are less successful in conveying spatial narratives than in traditional types of representation. In this study, a method has been proposed to develop the representation possibilities of the virtual reality environment by using the denotative and connotative meaning creation techniques of cinema. In the proposed method, meaning creation techniques of the cinema were used together with the interaction element of virtual reality, which is its most unique facility. By using the lighting technique between the denotative and connotative meaning creation methods of the cinema dynamically in the virtual reality medium according to the user interaction, introducing a spatial narrative to the user is directed. The discovery of the narrative possibilities of the virtual reality environment will enable it to be used more effectively as an architectural representation and moreover it will ensure this medium to be accepted as a new genre of art production.
Keywords: Architectural representation; computer aided architecture; computer aided design; representation; spatial perception; virtual reality; Architecture